Airport capacity and entry deterrence: Low cost versus full service airlines. (June 2020) - Valido, Jorge; Socorro, M. Pilar; Medda, Francesca
Abstract: We study entry deterrence in air transport markets with a full-service ( FS ) carrier (the incumbent) and a low-cost ( LC) carrier (the potential entrant). We consider a vertically differentiated product model where airlines have different operating cost and different generalized prices so they compete in ticket prices and frequencies. Thus, more frequency allows airlines to increase ticket prices without losing demand. In this context, we show that the incumbent may increase the frequency offered in order to deter the LC carrier entry. We show that if the airport capacity is low enough the LC carrier entry can be easily blocked or deterred. However, if the airport capacity is sufficiently high, the LC carrier entry must be accommodated. Regulators should take these results into account in order to promote competition among airlines. Highlights: We analyse competition between a full service (FS) and low cost (LC) carriers. Carriers compete in prices and frequency with vertically differentiated products. Depending on the airport capacity, the entry can be deterred or accommodated. A different system for allocating slots may favour competition among airlines. Regulators aiming to promote competition should force airports to expand capacity.